The Green Transformation and the Costs of Market Fundamentalism - Tom Krebs; Isabella Weber (Institute of Labor Economics (IZA), 2025)
The structural theory of green transformation acknowledges the complexity of the transformation process and suggests a state-led approach with green industrial policy at its core. In contrast, the market-fundamentalist approach to the transformation problem relies on carbon pricing and the assumption of smooth adjustment to rising market prices. We argue that the recent energy crisis in Germany provides a test of market fundamentalism. We show that the behavior of key macroeconomic variables contradicts the market-fundamentalist theory of green transformation. We also detail how mainstream economists and the policy establishment held on to their belief in self-regulating markets despite the empirical failure of market fundamentalism, which led to policy mistakes with large economic and political costs. Policy making based on market fundamentalism caused substantial damage to Germany's economy and helped the far-right Alternative for Germany (AfD) double its political support.
Keywords: E12; E32; E64; L50; L60; Q43; Q48; 330; inflation; energy crisis; market fundamentalism; green industrial policy; green transformation; fiscal austerity; price controls.